PENGALAMAN KOMUNIKASI ANAK DALAM INTERAKSI ROLEPLAY DI GAME ROBLOX - Weni Prilia; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Roblox is an online game platform based on user-generated content that allows children to build avatars, create stories, and interact in virtual spaces. This study focuses on children's communication experiences in roleplay interactions in Roblox. The main issue is not only how children play, but how they use symbols, roles, language, feedback, and virtual relationships to build shared meaning. This study uses an interpretive paradigm, a qualitative method, and narrative analysis based on Todorov's narrative flow. Data were collected through in-depth interviews with eight child informants who had experience playing roleplay in Roblox, especially in Metro Life, Brookhaven, and Adopt Me. The findings show that roleplay in Roblox becomes a virtual communication space where children build social relationships, express virtual identity, and negotiate shared stories. Children's experiences move through five narrative stages: initial equilibrium, disruption, recognition of disruption, attempt to repair, and new equilibrium. The disruption appears through toxic interaction, ignored messages, avatar mockery, chat censorship, and conflict in storylines. Children respond by staying silent, leaving the map, changing servers, apologizing, following group rules, or choosing safer friends. The study concludes that children are not passive users. They actively manage communication, build selective openness, and create symbolic convergence through avatars, roleplay families, circles, shared terms, and repeated stories.